The configuration of the on line sale of luxury productos in selective distribution system - Antón Juárez, Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
Being a member to a selective distribution network can be very positive for an official distributor. This is because the distributor can benefit from the prestige of the brand. This benefit has its opposite side because the official distributor must abide the rules that the owner of the network imposes contractually. One of the aspects in which the official distributor can see conditioned and affect its business activity is in relation to online sales. This is so because the owner of the network will be able to justify restrictions on the online sales of their official distributors in order to protect the prestige of the brand without violating European competition rules. This means that the official distributor could be prohibited from selling on certain e-commerce platforms. It could be said that the current situation benefits the holders of the official distribution networks, since covered by the European competition rules may incorporate clauses in the selective distribution contracts that allow them a great control over the online sale of their official distributors.